2013
DOI: 10.1111/sltb.12050
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Adolescent Suicide Attempters from Ideators: Examining the Interaction between Depression Severity and Alcohol Use

Abstract: This study examined whether depressed mood, frequency of alcohol use, and their combination differentiated non-suicidal adolescents from those with suicidal ideation and adolescents with suicidal ideation from those who have made a suicide attempt. Hierarchical logistic regressions indicated that frequency of alcohol use did not differentiate non-suicidal adolescents from those with current suicidal ideation, but severity of depressed mood did so. In contrast, alcohol use was a significant differentiating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 33 publications
(41 reference statements)
5
39
2
1
Order By: Relevance
“…In our sample of youth in primary care clinics, of 109 variables, only two (current depressive symptoms and lifetime history of alcohol use) were necessary to distinguish three groups of self‐harming youth: NSSI with no suicidal ideation or attempts (NSSI Only); NSSI with history of suicidal ideation (NSSI + Ideation); and NSSI with history of suicide attempt (NSSI + Attempt). Consistent with existing research, suicide risk among the youth in our sample increased with the severity of depressive symptoms and among youth who reported both moderate to high levels of depression and alcohol use (McManama O'Brien, Becker, Spirito, Simon, & Prinstein, ). In this study, we found that current depressive symptoms are perhaps the best predictor of suicidal ideation and that the combination of current depressive symptoms and a history of ever drinking alcohol is the best predictor of attempts among youth engaging in NSSI.…”
Section: Discussionsupporting
confidence: 88%
“…In our sample of youth in primary care clinics, of 109 variables, only two (current depressive symptoms and lifetime history of alcohol use) were necessary to distinguish three groups of self‐harming youth: NSSI with no suicidal ideation or attempts (NSSI Only); NSSI with history of suicidal ideation (NSSI + Ideation); and NSSI with history of suicide attempt (NSSI + Attempt). Consistent with existing research, suicide risk among the youth in our sample increased with the severity of depressive symptoms and among youth who reported both moderate to high levels of depression and alcohol use (McManama O'Brien, Becker, Spirito, Simon, & Prinstein, ). In this study, we found that current depressive symptoms are perhaps the best predictor of suicidal ideation and that the combination of current depressive symptoms and a history of ever drinking alcohol is the best predictor of attempts among youth engaging in NSSI.…”
Section: Discussionsupporting
confidence: 88%
“…Only the presence of a suicide plan [3, 12] and a history of self-harm or suicide have consistently been shown to predict the progression from suicide ideation to an attempt [3, 14, 16, 17]. Factors, such as mental illness [3, 12, 14, 18–21], substance abuse [3, 12, 19], sex [3, 12, 20–22], age [3, 12, 21, 22], marital status [3, 19], social interactions and belonging [14, 19], and life stressors [14, 18] have had conflicting findings. Other potential risk factors, such as financial strain [23, 24] and physical illness [25, 26], have not been studied as factors that may distinguish suicide ideators and attempters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theory and research support the conceptualization of suicidal thoughts and behaviors as highly complex and dynamic phenomena characterized by substantial heterogeneity. Different variables predict suicide ideation, suicide planning, suicide attempts, and death by suicide (Dhingra, Boduszek, & O'Connor, ; Khazem & Anestis, ; McManama O'Brien, Becker, Spirito, Simon, & Prinstein, ; Simon et al., ; Spokas, Wenzel, Brown, & Beck, ; Taliaferro & Muehlenkamp, ; see May & Klonsky, ; for a review). Different predictors are effective in different populations (Kessler, Berglund, Borges, Nock, & Wang, ; Nock et al., ).…”
mentioning
confidence: 99%
“…. Many studies of adults support the role of hopelessness as a longitudinal predictor of suicidality, even after controlling for depressive symptoms, in both adults (Beck, Brown, Berchick, Stewart, & Steer, 1990;Beck, Steer, Beck, & Newman, 1993;Brown, Beck, Steer, & Grisham, 2000;Chioqueta & Stiles, 2003;Steer, Kumar, & Beck, 1993) and adolescents (Asarnow et al, 2011;Mazza & Reynolds, 1998;Mustanski & Liu, 2013;Stewart et al, 2005). Drawing on this research, Wenzel and Beck (2008) refined Beck's cognitive model, differentiating between cognitive processes (such as attentional biases toward suicide-relevant stimuli) and maladaptive cognitive content (such as hopelessness) in the etiology of suicide ideation.…”
mentioning
confidence: 99%